Effectiveness of a computer game for recognizing and understanding facial emotions in hearing-impaired children - Ghanat, Mozhgan (Revija za elementarno izobraževanje, 2025)
The present study evaluates the effectiveness of the EMOFIT computer game on the recognition and understanding of facially expressed emotions in 6-10- year-old hearing-impaired children. This quasi-experimental, pre-test-posttest design study, with control and experimental groups, was conducted with the participation of thirty children. The results showed significant improvement in emotion understanding, especially in adaptation (e.g., ?2 = 0.84), with slight improvement in naming (e.g., ?2 = 0.57). Results suggest that games like EMOFIT can effectively improve impaired social skills and emotional development among children.
Keywords: children; computer game; facial emotion recognition; facial emotion understanding; Gluhi in naglušni; hearing impairments; okvare sluha; otroci; prepoznavanje obraznih čustev; računalniška igra; razumevanje obraznih čustev